Um olhar sobre velhice e envelhecimento: percepção de mulheres patobranquenses - Rocha, Marcia Antunes da (2025)
Currently, we are facing an increase in the elderly population, especially with regard to the greater life expectancy of women compared to men. This reality invites us to reflect on the transformations that have been occurring in the lives of these individuals, especially women. In this perspective, the general objective of the study is to analyze how women participating in the Social Assistance Reference Center (CRAS) of Pato Branco-PR experience the aging process. This is an exploratory research of a qualitative nature. The study was carried out at the CRAS, in the neighborhoods of São João and Bairro Alvorada, both considered highly vulnerable. The sample consisted of 10 women over 60 years old, who were regular attendees of the institution. For data collection, we chose the semi-structured interview. Discussion and analysis were subjected to content analysis. Based on the grouping of the nuclei of meaning, the following categories were formed: childhood, youth; marriage; living with children; spaces of sociability; their life projects; leisure; illness; and the role of CRAS in this debate and perceptions about aging. It was possible to learn from the elderly women that aging is related to the loss of autonomy. For these elderly women, the ability to perform daily tasks and remain active is fundamental to their self-perception of youth. They refuse to accept old age as a phase of dependence and inactivity, challenging stereotypes and seeking to maintain a young and active mentality. The relationship with appearance is also important, with some highlighting vanity and the desire to dress up as elements that reinforce their feeling of youth. On the other hand, some women accept the limitations imposed by age calmly, recognizing the physical challenges and the need to adapt to the new reality. This acceptance is often accompanied by gratitude for the life experiences accumulated and the respect received from the community.